The dictionary of financial risk management - Gastineau, Gary L. (Frank J. Fabozzi Associates, 1999)
The Dictionary of Financial Risk Management includes listings of common acronyms, profit/loss diagrams of new financial instruments, and extensive coverage of derivatives and quantitative techniques. This invaluable reference guide provides comprehensive definitions of the key terms and concepts that many financial professionals need to know on a day-to-day basis